Creativity Between the Illustrator and Non-Illustrator Writers in Applying Pragmatic Discourse to Narrative Pictures - Irfan Hamonangan Tarihoran; Sartika Sartika (Universitas Galuh, 2026)
The present study examined creativity in shaping English-language children's stories through instructions to arrange random pictures into narratives. The objectives of this study were to identify, i.e. i) significant differences in creativity in applying pragmatic discourse to narrative pictures between illustrator and non illustrator writers; ii) how pragmatic discourse was applied to narrative pictures by both groups of writers; and iii) how narrative pictures were arranged. A total of 40 college students consisting of 20 illustrator writers and 20 non illustrator writers participated in this study. The present study employed a mixed-method sequential explanatory design. Quantitative data were obtained from creativity tests, specifically the element of fluency associated with pragmatic discourse by Blum Kulka. Quantitative data analysis employed non-parametric tests, specifically the Mann-Whitney U test. The quantitative analysis was supported by qualitative data from closed-ended questionnaires and interview results. The pragmatic approach through picDRT, in conjunction with Blum Kulka's pragmatic discourse, served to elucidate the problem. The findings indicated that implicature as a component of pragmatic discourse, exhibited substantial disparities between both groups of writers; with the illustrator writers demonstrating a higher degree of dominance compared to the non-illustrator writers. However, although not significantly different, the non-illustrator writers can be more dominant in terms of adaptation to context. Furthermore, the non-illustrator writers tend to prioritize narration and continuity-related coherence relations more than the illustrator writers.